Identified gaps and opportunities in perinatal healthcare delivery for women in treatment for opioid use disorder. Issue 4 (October 2021) - Alexander, Karen; Short, Vanessa; Gannon, Megan; Goyal, Neera; Naegle, Madeline; Abatemarco, Diane J.
Background: Pregnancy and the delivery of an infant mark a unique time of engagement in healthcare for women in treatment for opioid use disorder (OUD). The American College of Obstetrics and Gynecology calls for a comprehensive approach to perinatal healthcare delivery for pregnant women with OUD in order to facilitate improved health outcomes and increase patient-provider collaboration. Yet, there is little knowledge regarding the perceptions of women with OUD regarding the current delivery of healthcare which could inform a personalized, tailored approach to perinatal healthcare delivery. Methods: Four focus groups consisting of 22 women with OUD were conducted, transcribed, and analysed using qualitative thematic analysis methodology. Results: Women reported an overall lack of preparation for the birth and neonatal healthcare experiences and identified opportunities for greater support by the healthcare team. Women emphasized the desire for evidence-based preparation from trusted sources about delivery, neonatal abstinence syndrome, breastfeeding, and how their medications affect their pregnancy and baby. Women reported receiving a varied amount of support from healthcare providers in their transition to motherhood, but women predominantly reported receiving emotional and informational support from their mothers and partners. Conclusions: The knowledge obtained in this study points to gaps in perinatal healthcare delivery for women with OUD. Improving the delivery of perinatal healthcare may contribute to increased engagement by women with OUD, and ultimately improve outcomes for a vulnerable population.